HUBUNGAN INISIASI MENYUSU DINI TERHADAP PEMBERIAN ASI EKSKLUSIF DI UPT PUSKESMAS GAJAH MADA KABUPATEN INDRAGIRI HILIR - Sandra Harianis (Jurnal Kesehatan Husada Gemilang, 2018)
Early breastfeeding initiation is the process of immediate infant feeds after birth, where the baby himself is allowed to find his mother’s nipple. Exclusive breastfeeding and correct breastfeeding are reliable means to build quality of human resources. The Government of Indonesia supports the WHO and UNICEF policies that recommend the early breastfeeding initiation is as “life-saving” because it can save 22% of babies die before a month. According to the report of delivery at UPT Puskesmas Gajah Mada, Indragiri Hilir in 2014, there were 216 mothers of 222 delivery who did the initiation of early breastfeeding. This study drives to determine whether there is a relationship between early breastfeeding initiations and exclusive breastfeeding at UPT Puskesmas Gajah Mada Indragiri Hilir in 2014. The type of this research is cross sectional analytic design. The research was done on 9 to 14 of June 2014 at UPT Puskesmas Gajah Mada. The sampling technique of this research was purposive (60 people). Data was gained through checklist and analyzed by using Chi Square. The results showed that there were 46 people (83, 6%) who initiated the early breastfeeding, 9 people (16, 4%) who did not, 41 people (74, 5%) who exclusively breastfeed their infants, and 14 people (25, 5%) who did not. Statistically it can be concluded that there is relationship between early breastfeeding initiation and exclusive breastfeeding at UPT Puskesmas Gajah Mada Indragiri Hilir (p = 0,007). It is expected that UPT Puskesmas Gajah Mada Indragiri Hilir evaluate the management of early breastfeeding initiation on mothers to their babies as it is crucial, especially in supporting the exclusive breastfeeding.